2015
DOI: 10.1159/000430885
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Influence of Tissue Inhibitor of Matrix Metalloproteinase-1 in Patients with Mild to Moderate Coronary Artery Lesions in a Chinese Population: A 7-Year Follow-Up Study

Abstract: Objectives: Matrix metalloproteinase-9 (MMP-9), tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) and their ratio (MMP-9/TIMP-1) are involved in multiple processes that are associated with coronary heart disease and are especially associated with cardiovascular events. However, few long-term population-based clinical studies have evaluated the role of these factors in cardiovascular events in a Chinese population. Methods: A prospective study was performed on 560 patients with mild to moderate coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
13
1
1
Order By: Relevance
“…MMP-9 levels have previously been associated with clinical events in numerous reports [25,28], although some of these are contradictory [29]. In our study, circulating MMP-9 levels and the MMP-9/TIMP-1 ratios were numerically, but not significantly, higher in patients experiencing clinical events during follow-up.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…MMP-9 levels have previously been associated with clinical events in numerous reports [25,28], although some of these are contradictory [29]. In our study, circulating MMP-9 levels and the MMP-9/TIMP-1 ratios were numerically, but not significantly, higher in patients experiencing clinical events during follow-up.…”
Section: Discussioncontrasting
confidence: 43%
“…We have previously shown that genetically determined high circulating levels of MMP-9 were associated with new clinical events in patients with stable coronary artery disease and the metabolic syndrome [30]. TIMP-1 has previously been associated with clinical outcome in Caucasians with AMI and in a Chinese population with coronary artery lesions [15,29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the manuscript that is the focus of this editorial, Wang and colleagues investigated whether plasma MMP-9 and TIMP-1 levels as well as the MMP-9/TIMP-1 ratio could be used as biomarkers to predict future cardiovascular events in Chinese patients with mild to moderate coronary artery stenosis [3]. Immediately after diagnosis, plasma levels of MMP-9 and TIMP-1 were measured, and the patients were followed for a median of 64 months.…”
mentioning
confidence: 99%
“…Of note, TIMP-1 suppresses microvascular endothelial cell migration through both MMP-dependent and MMP-independent mechanisms [11]. The MMP independent roles of TIMP-1 may, at least partially, explain why TIMP-1, but not MMP-9, independently predicted MACEs risk in the Wang et al study [3]. …”
mentioning
confidence: 99%